Decoupling company growth from employee compensation: A study of publicly listed firms in indonesia - Elperida Juniarni Sinurat; Junika Napitupulu (Journal of Innovation in Business and Economics, 2024)
This study aims to explore the relationship between company growth and employee compensation in publicly listed companies on the Indonesia Stock Exchange from 2019 to 2021. Using Ordinary Least Squares (OLS) method and a total sample of 982 companies, the study reveals several significant findings. The results indicate that there is no significant relationship between company growth and increased employee compensation, and vice versa. Company growth is more influenced by the level of assets held, while employee compensation is more influenced by company leverage. Interestingly, increases in assets and Tobin's Q actually decrease employee compensation. Managerial implications of these findings suggest that strategies for enhancing company growth and employee compensation policies need to be managed independently based on the specific factors affecting each aspect. Focusing on asset enhancement and effective leverage management is key to efficiently managing company growth and compensation policies. This study provides new insights into the dynamics between company growth and employee compensation, emphasizing the importance of integrated strategic management for achieving long-term sustainability and success.